When floods strike close to home. Issue 1 (5th March 2019) - Rowley, David; Buckler, Mick; Barnett, Joanne
Abstract : Flooding and the impact on the highway network is a major influence in the design and implementation of municipal emergency response and disaster relief planning. Worcestershire is a low-lying shire county in the UK West Midlands, bordered to the southwest by the Malvern Hills. Dissected by a number of major waterways, most notably the rivers Severn, Avon and Teme, and the Droitwich, Staffs and Worcester, Grand Union and Stratford upon Avon canals – a combination of both tidal and non-tidal waterways – the impact of prolonged inclement weather can have far-reaching effects on the effectiveness of the highway network and its ability to perform adequately. The year 2013 saw the worst rainfall since records began; this paper outlines actions taken to minimise disruption to the travelling public, methods of working and learning achieved to prepare for future occurrences in light of predicted climate change and its effect on weather patterns.